Historical-Cultural Psychology in Research Groups in the CNPq Directory in Brazil - Asbahr, Flávia da Silva Ferreira [UNESP]; de Souza, Marilene Proença Rebello; Barroco, Sonia Mari Shima (FapUNIFESP (SciELO), 2024)
This article presents an overview of research groups that use Historical-Cultural Psychology as a theoretical framework, registered in the Directory of Research Groups of the Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq). A “state of knowledge” study was held. 115 groups were found, and the following data stand out from the analysis of their descriptions: terms used to name the theory; knowledge areas; geographic distribution; nature of the group’s institution; foundation year; and main research topics in the areas of psychology and education. As a result, it is pointed out: that semantic dispersion concerning the theory naming; increase in groups researching public policies; and insertion of contemporary themes such as racism and gender. It is concluded that the above panorama makes it possible to better understand the research interests carried out by Historical-Cultural Psychology and the challenges to be faced.
Psicologia Histórico-Cultural nos Grupos de Pesquisa no Diretório do CNPq no Brasil
Keywords: CNPq; historical-cultural psychology; research groups; state of knowledge